2004
DOI: 10.1038/sj.ejcn.1601836
|View full text |Cite
|
Sign up to set email alerts
|

Gender influence on plasma triacylglycerol response to meals with different monounsaturated and saturated fatty acid content

Abstract: Objective: Both gender and meal fatty acid composition modulate postprandial triacylglycerol (TAG) metabolism, but little information exists on their interaction. We compared postprandial TAG concentrations in men and women after test meals differing in the proportion of monounsaturated (MUFA) and saturated fatty acids (SFA). Subjects: Nine men (body mass index, BMI: 24.572.3 kg/m 2 ) (mean7s.d.) and 10 premenopausal women (BMI: 21.271.7 kg/m 2 ), young and healthy, habituated to a relatively high MUFA diet. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 38 publications
6
29
0
Order By: Relevance
“…This effect was not confirmed by a meta-analysis, which selected a minority of the reports [Gardner and Kraemer, 1995]. The increase in postprandial TGs is higher from MUFAs than from SFAs and PUFAs [Nielsen et al, 2002;Koutsari et al, 2004].…”
Section: Plasma Lipids and Cvdmentioning
confidence: 89%
“…This effect was not confirmed by a meta-analysis, which selected a minority of the reports [Gardner and Kraemer, 1995]. The increase in postprandial TGs is higher from MUFAs than from SFAs and PUFAs [Nielsen et al, 2002;Koutsari et al, 2004].…”
Section: Plasma Lipids and Cvdmentioning
confidence: 89%
“…Therefore, variability in the contribution of TGs coming from the contents of an earlier meal may help explain some of the discrepancy between the studies described above. Additionally, because the TG response to a high-fat meal is different between men and women (Couillard et al 1999;Horton et al 2002;Knuth and Horowitz 2006;Koutsari et al 2004;Sopowski et al 2001), the discrepancy between these studies may also be due in part to sex-related differences in the response to the coingestion of CHO and fat. The metabolic effects of adding Values are means ± SEM, n = 9 for each sex.…”
Section: Introductionmentioning
confidence: 89%
“…Previous work has found that the plasma TG response after a meal is often greater in men than in women (Couillard et al 1999;Horton et al 2002;Koutsari et al 2004;Sopowski et al 2001), and this sex-specific difference in lipemic response to a fat meal may contribute to the delayed development of CVD in women compared with men (Rosamond et al 2007). More specifically, we recently demonstrated that alterations in chylomicron metabolism (i.e., prolongation of chylomicrons in men compared with women), explained much of the sex-related difference in post-prandial lipemia after a fat meal (Knuth and Horowitz 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, two studies evaluated plasma free fatty acid kinetics in men and women after consumption of an energy-adjusted mixed meal and found that the relative (to basal values) meal-induced decrease in free fatty acid Ra was the same in men and women [87,88]. Similarly, the suppression of plasma free fatty acid concentration following ingestion of a mixed meal adjusted for sex differences in energy requirements was found to be the same in men and women [8991]. However, the suppression of plasma free fatty acid concentration after a standard OGTT is typically greater in women than in men [38,66,73,92,93], most likely because the greater glucose/insulin challenge in women.…”
Section: Sex Differences In the Control Of Adipose Tissue Lipolysis Bmentioning
confidence: 99%